Wpływ prac wiertniczych na właściwości gleb oraz stan zdrowotny drzew w rejonie Kopalni Soli "Solino" S.A. w Górze k. Inowrocławia = Influence of salt drilling operation on soil properties and the state of health of trees in the area of the Salt Mine "Solino" SA in Góra near Inowrocław - Hulisz, Piotr; Cyzman, Wiesław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper aimed at analysing the influence of salt drilling operation on soil properties and the state of health of trees. The study was conducted in the area of the salt mine in Góra near Inowrocław (north-central Poland). Due to the impact of aerosols, the high salt accummulation in soils in the 50 m zone around the drilling site was stated.
Keywords: zasolenie gleb; NaCl; stres solny; wysad solny; górnictwo soli; soil salinity; salt stress; salt dome; salt mining